2013
DOI: 10.1038/nclimate1756
|View full text |Cite
|
Sign up to set email alerts
|

A global standard for monitoring coastal wetland vulnerability to accelerated sea-level rise

Abstract: Friess, Daniel A.; Krauss, Ken W.; Cahoon, Donald R.; Guntenspergen, Glenn R.; and Phelps, Jacob, "A global standard for monitoring coastal wetland vulnerability to accelerated sea-level rise" (2013). USGS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(165 citation statements)
references
References 76 publications
4
157
1
3
Order By: Relevance
“…This is because the main research interest on sediment dynamics is predominantly focused on long-term accretion rates to see whether mangroves can keep up with sea-level rise (see e.g. Woodroffe, 1995;Lovelock et al, 2011;McKee, 2011;Webb et al, 2013). However our results clearly demonstrate the importance of frequent measurements of sediment dynamics (i.e.…”
Section: Discussioncontrasting
confidence: 40%
“…This is because the main research interest on sediment dynamics is predominantly focused on long-term accretion rates to see whether mangroves can keep up with sea-level rise (see e.g. Woodroffe, 1995;Lovelock et al, 2011;McKee, 2011;Webb et al, 2013). However our results clearly demonstrate the importance of frequent measurements of sediment dynamics (i.e.…”
Section: Discussioncontrasting
confidence: 40%
“…Second, while our one low marsh core exhibits anomalously low CAR relative to the high cores in which CAR was estimated, the single core does not possess sufficient statistical power to draw conclusions about differences between average low and high marsh CAR in Clayoquot Sound because of regional heterogeneity SAR and CAR within and between marshes. Previous studies of marsh accretion dynamics have 5 demonstrated variability in SAR on scales as small as one meter due to such influences as recent ecological disturbance (Webb et al 2013), water table height and soil drainage (Craft 2007), and variable mineral sediment deposition from freshwater drainage (Callaway et al 2012). In our case, a power analysis suggests that at least nine cores measured for CAR would be required to confidently compare the means of low marsh and high marsh cores.…”
Section: Low Marsh Car 10mentioning
confidence: 99%
“…The SET method measures VLM w of the substrate overlying the SET rod base, which ideally is set on bedrock, by direct measurement of the wetland surface relative to the SET rod base (Cahoon et al 1995;Cahoon et al 2002b;Webb et al 2013;Figs. 1 and 2).…”
Section: Wetland Elevation Changementioning
confidence: 99%
“…In addition, global evaluations of wetland elevation trends using the high resolution (mm/y) surface elevation table-marker horizon (SET-MH) method (Cahoon et al 1995) wetland elevation trends vary within and among wetlands, ranging from positive to negative slopes influenced by both surface vertical accretion and erosion, and subsurface subsidence and expansion processes . The SET-MH method is currently used in 29 countries on six continents in both temperate and tropical coastal regions to evaluate elevation dynamics in primarily salt marsh and mangrove environments (Webb et al 2013). Unlike the upland habitats where tide gauges are located, salt marshes and mangrove forests are able to alter their surface elevation by trapping sediments brought in by the tide, and through belowground production and accumulation of roots and rhizomes.…”
Section: Introductionmentioning
confidence: 99%